Bridging Experience and Intention: The Mediating Role of Outcome Expectations in Social Entrepreneurship among Creative Economy Actors - Rezky, Muhammad Iqbal; Sojanah, Janah; Rasto, Rasto (UI Scholars Hub, 2025)
This study explores the role of outcome expectations in mediating the influence of prior experience on social entrepreneurship intention in the creative economy sector of Indonesia. Despite the increasing interest in social entrepreneurship, research on the factors driving the intention to become a social entrepreneur remains scarce. This study employed the Social Cognitive Career Theory (SCCT) as a theoretical framework to investigate social entrepreneurship as a career choice, focusing on the influence of outcome expectations on social entrepreneurship intention. A quantitative explanatory survey was conducted with 290 creative economy actors in Bandung through questionnaires. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that positive outcome expectations mediate the influence of prior experience on social entrepreneurship intention, highlighting the importance of outcome expectations in shaping social entrepreneurship intention. Prior experience in addressing social issues indirectly drives social entrepreneurship intention through positive outcome expectations. These findings underscore the need to cultivate positive outcome expectations in social entrepreneurship training programs to enhance entrepreneurial self-efficacy and motivation. However, this study is limited to creative economy actors in Bandung, affecting its generalizability. Future research could explore additional mediating variables or apply this model to different entrepreneurial sectors. This study contributes to the literature by integrating SCCT into social entrepreneurship, offering a novel perspective on how prior experience shapes entrepreneurial intention.